Labour Adjustment and Efficiency in Hungary - Gabor Korosi (Hungarian Academy of Sciences, Institute of Economics, Labour Research Department, 2002)
Transition from socialist to market economy brought drastic changes to the Hungarian labour market. Employment fell by 1.6 million, i.e., by more than 25% during the early transition period, while unemployment jumped from practically nil to over 14% within four years. The rapid economic growth of the recent years could only create relatively few jobs, even though the unemployment rate continuously declined, and is less than 6% since 2001. This paper describes labour adjustment after the transitional recession, and its relationship to corporate efficiency during the recovery period, based on a panel of medium-sized and large Hungarian firms. Labour demand is also related to firm level productive efficiency.
Keywords: J23; D21; C23; 330; labour demand; productive efficiency; firm in transition economy